CLINICAL CHARACTERISTICS AND BLOOD PRESSURE TIME-COURSE IN THE YOUNG ACCORDING TO HYPERTENSION SUBTYPE. (April 2021) - Saladini, Francesca; Mos, Lucio; Vriz, Olga; Mazzer, Andrea; Fania, Claudio; Rattazzi, Marcello; Palatini, Paolo
Abstract : Objective: The prognostic significance of different hypertension subtypes in youth is still debated. The aim of the study was to investigate baseline clinical and haemodynamic characteristics and blood pressure (BP) time-course in young subjects with systolic hypertension compared to other hypertension subtypes. Design and method: We investigated 1206, 18-to-45-year old subjects from the HARVEST: 81 normotensives (NT), 146 isolated systolic hypertensives (ISH), 281 isolated diastolic hypertensives (IDH) and 698 systolic-diastolic hypertensives (SDH). Baseline haemodynamic and metabolic characteristics, BP and heart rate (HR) changes during a 7-year follow-up were measured. Age-and-sex-adjusted ANCOVA analysis was used for group comparisons. Results: ISH were younger and more frequently males compared to others (25.6 ± 6.6 years, p < 0.001), were thinner compared to SDH (24.6 ± 2.6 vs 25.8 ± 3.6 kg/m2, p = 0.028). HR was higher among ISH (75.7 ± 9.4 bpm) and SDH (75.8 ± 9.7) compared to other categories (p < 0.001). ISH were more active in sports (55.5%) compared to others (p < 0.001). Metabolic characteristics were not significantly different among groups. Systolic white-coat effect was higher among ISH (17.6 ± 12.4 mmHg) compared to others (p < 0.001). Cardiac output was significantly higher among ISH (6.3 ± 1.2 ml/min) compared to NT and IDH (p < 0.001); ISH had similar peripheral resistances to NT and lower than IDH and SDH (p < 0.001). Small and large artery compliance was greater and central systolic BP and augmentation index were lower among NT and ISH than IDH and SDH, but differences were not statistically significant (N = 360). During follow-up systolic BP decreased (-7.6 ± 14.4 mmHg) among ISH, while it increased among NT and IDH (p < 0.001). HR decreased in all categories but to a higher extent among ISH (-3.8 ± 10.9 bpm) and SDH (-3.4 ± 10.8 bpm, p = 0.002 versus NT). The percent of patients who started pharmacological treatment during follow-up was: 70.6% among SDH, 54.1% among IDH, 41.1% among ISH, and 39.5% among NT (p < 0.001). Conclusions: Young ISH had greater white coat effect, hyperkinetic circulation and lower peripheral resistances compared to other hypertension categories, while arterial distensibility parameters did not differ significantly among groups. Subjects with ISH showed a favourable time-course of BP and HR with a lower percent of subjects needing antihypertensive treatment, suggesting a lower risk profile.